Threat of grade retention, remedial education and student achievement: Evidence from upper secondary schools in Italy - Erich Battistin; Antonio Schizzerotto (Institute for the Study of Labor (IZA), 2012)
We use a reform that was recently implemented in Italy to investigate the effects on academic achievement of more stringent requirements for the admission to the next grade at upper secondary school. We study how such effects are mediated by changes in family and school inputs, and in the student commitment to learn all school subjects including those usually considered as marginal components of the curriculum. Geographical discontinuities in the implementation of the reform allow us to set out the comparison of similar students undergoing alternative progression rules, and to shed light on whether, and to what extent, the reform has worked as a tool to improve short-term achievement gains. We document differential effects across curricular tracks, picturing at best - depending on the data employed - a marginal improvement for students in academic schools. We instead find sharp negative effects of the reform in technical and vocational schools, where the students enrolled come from less privileged backgrounds. These findings are accompanied by a substantial increase in the number of activities out of the normal school hours in technical and vocational schools, but not in academic schools. Also, we find that the reform has left unchanged the various family inputs that we consider, and that parents did not provide extra economic support to students facing an increased threat of grade retention. However, in contrast with the documented effects on achievement, we find that schools reacted to the additional administrative burdens and costs imposed by the reform by admitting more students to the next grade. We thus conclude that the reform has had a negative effect on motivation and engagement of the most struggling students, thus exacerbating existing inequalities.
Keywords: C31; I24; I28; 330; policy evaluation; quasi experimental designs; remedial education; Weiterführende Schule; Bildungsreform; Wirkungsanalyse; Studierende; Bildungsabschluss; Feldforschung; Italien